2019
DOI: 10.1186/s13071-019-3492-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-read sequencing reveals a 4.4 kb tandem repeat region in the mitogenome of Echinococcus granulosus (sensu stricto) genotype G1

Abstract: Background Echinococcus tapeworms cause a severe helminthic zoonosis called echinococcosis. The genus comprises various species and genotypes, of which E. granulosus ( sensu stricto ) represents a significant global public health and socioeconomic burden. Mitochondrial (mt) genomes have provided useful genetic markers to explore the nature and extent of genetic diversity within Echinococcus and have und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 78 publications
2
40
0
Order By: Relevance
“…Similar regions in other studies of mt genomes have also been shown as problematic [46,47]. Therefore, the PacBio single-molecule real-time sequencing method has been used by researchers in recent studies to characterize long and difficult to sequence repetitive regions of flatworm mitogenomes [48,49]. Nonetheless, the coding regions of the mt genomes of Brachylecithum sp.…”
Section: Gene Organization Size and Nucleotide Content Of Mitogenomesmentioning
confidence: 80%
“…Similar regions in other studies of mt genomes have also been shown as problematic [46,47]. Therefore, the PacBio single-molecule real-time sequencing method has been used by researchers in recent studies to characterize long and difficult to sequence repetitive regions of flatworm mitogenomes [48,49]. Nonetheless, the coding regions of the mt genomes of Brachylecithum sp.…”
Section: Gene Organization Size and Nucleotide Content Of Mitogenomesmentioning
confidence: 80%
“…All 12 protein-encoding genes, 22 tRNAs and two rRNAs had high sequence similarities (> 99.2%) to those in published mitochondrial genomes and occurred in the same order. However, there is clear evidence [17,18,38] that conventional sequencing methods are not suited to the sequencing of long non-coding regions in mitochondrial genomes. This obstacle has been overcome through the use of nanopore-sequencing, which bodes well for future mitochondrial genome investigations.…”
Section: Overcoming the Challenges Of Sequencing The Tandem-repetitivmentioning
confidence: 99%
“…With the advent of 'short-read' sequencing (e.g., Illumina) came the confidence that sequencing at high coverage in a high throughput manner would readily allow the sequencing and assembly of complete mitochondrial genomes, because of their relatively small size (~14 kb ± 1 kb in flatworms; [14]). However, there have been challenges with sequencing through tandem-repetitive elements and regions with a biased nucleotide composition using Sanger and short-read technologies [16][17][18], and little attention has been paid to the impact of these issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA features exploration. Since a more complete mitochondrial genome of E. granulosus has been published[45], we replaced the mitochondrial sequence of Tsai, et al[44] with the most updated one. Read pairs from E. granulosus annotated samples and E. multilocularis annotated samples were pooled separately and remapped with BWA (v0.7.16)[46] to their corresponding references to get the mapping positions and fragment length.…”
mentioning
confidence: 99%